Joint range–velocity deception jamming suppression for SIMO radar. Issue 1 (1st January 2019) - Huang, Datong; Cui, Guolong; Yu, Xianxiang; Ge, Mengmeng; Kong, Lingjiang
Abstract : This study deals with the problem of range–velocity joint deception jamming suppression for a single‐input multiple‐output (SIMO) radar system. The Doppler diversity and spatial geometric correlation are exploited to distinguish the jamming and multiple moving targets. First, the echoes in each receiver are mapped into range–Doppler plane by pulse compression and slow‐time Fourier transform operations. Then, in each receiver, the range and Doppler frequency of the targets are extracted. Third, based on differences between the physical target echoes and the jamming signals in both range and Doppler dimensions, two identification algorithms are developed to discriminate the false targets in fusion centre. Finally, through numerical simulations, the performance of the proposed suppression scheme is evaluated, showing its capability to suppress the range–velocity joint deception jamming and locate the multiple physical targets with high precision.